Checklist of the family Megalopodidae Latreille (Coleoptera: Chrysomeloidea); a synthesis of its diversity and distribution - Rodríguez-Mirón, Geovanni M. (Zootaxa, 2018)
A checklist of the Megalopodidae of the world is presented. A total of 582 species in 29 genera and 11 subgenera are recognized belonging to the three subfamilies. The subfamilies, genera, and species are listed in alphabetical order. For each species, synonymous names and the geographical distribution by country is provided. The most diversified subfamily is Megalopodinae with 480 species and 24 genera. The Neotropical biogeographic region has the highest diversity of Megalopodidae, followed by the Ethiopian region. The knowledge of Megalopodidae is limited, and is remarkably biased by country. A significant increase in geographic and taxonomic information is needed in order to fill these knowledge gaps. The following taxonomic and nomenclatural changes are proposed: 1) type species are designated for the genera Macrolopha Weise and Falsomegalopus Pic. 2) Zeugophora novobicolor Rodríguez-Mirón is proposed as new replacement name of Zeugophora bicolor. 3) The following taxa are reinstated in the genera Temnaspis: T. speciosus Baly, T. arida Westwood, and T. nigriceps Baly. 4) Falsotemnaspis luteimembris Pic is proposed as new synonym (= F. lacordairei (Westwood)). 5) The next new combinations are proposed: Macrolopha bicolor (Jacoby), M. carinata (Bryant), M. centromaculata (Jacoby), M. costatipennis (Pic), M. dollmani (Bryant), M. hargreavesi (Bryan), M. mashuana (Jacoby), M. murrayi (Baly), M. neavei (Bryant), M. nyassae (Bryant), M. suturalis (Clavareau), M. variabilis (Westwood), M. aeneipennis (Weise), M. notaticollis (Pic), M. parvula (Weswood), M. theresae (Pic), M. tricoloripes (Pic) and Falsotemnaspis lacordairei (Westwood).